2020
DOI: 10.32479/ijefi.9294
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study in Albania of Foreign Direct Investments and Economic Growth Relationship

Abstract: Albania has managed to attract increasing foreign direct investments (FDI) inflows as a result of achieving political and macroeconomic stability, improving the business climate and legislation. FDI is an essential source of sustained economic growth for Albania, bringing in capital investment, advanced technology, and highly qualified management. FDIs have helped the country finance existing account deficits, further develop the financial sector, and increase employment possibilities. This paper aims to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Hansen and Rand (2006) assessed the FDI–growth nexus in a set of 31 developing economies, and the results revealed a long-run impact of FDI inflows on the economic growth of host country. Cakerri et al. (2020) also found a long-run relationship between FDI and economic growth.…”
Section: Review Of Literaturementioning
confidence: 84%
See 1 more Smart Citation
“…Hansen and Rand (2006) assessed the FDI–growth nexus in a set of 31 developing economies, and the results revealed a long-run impact of FDI inflows on the economic growth of host country. Cakerri et al. (2020) also found a long-run relationship between FDI and economic growth.…”
Section: Review Of Literaturementioning
confidence: 84%
“…Hansen and Rand (2006) assessed the FDIgrowth nexus in a set of 31 developing economies, and the results revealed a long-run impact of FDI inflows on the economic growth of host country. Cakerri et al (2020) also found a long-run relationship between FDI and economic growth. Mowlaei and Intezar (2021) studied the FDIgrowth relationship in a set of 30 Islamic countries and found a positive impact of FDI on economic growth.…”
Section: Review Of Literaturementioning
confidence: 84%
“…In the long term, technology implementation has an insignificant and positive relationship with economic growth. This means that technological developments are not sufficient to affect long-term economic growth (Lorena Cakerri, et al, 2020). Meanwhile (Robert Solow, 1970) proves that advances in technology, skills and skills of the workforce can affect economic growth.…”
Section: Technology Implementation and Economic Growthmentioning
confidence: 99%
“…In an attempt to overcome non‐stationarity in data series, a unit root test coupled with co‐integration regression following Engle and Granger (1987) and vector error correction models (VECM) following Johansen and Juselius (1990) have been widely used (see, e.g., Alexander & Johnson, 1992; Barkoulas et al, 2003; MacDonald & Taylor, 1991; McFarland et al, 1994). Recent applications of VECM models include Ali and Mingque (2018), Camba (2020), Cakerri et al(2020), Kuo (2016, 2018), and Teniwut et al (2019). Results from these studies, however, are mixed.…”
Section: Literature Reviewmentioning
confidence: 99%